Wind turbine ( wind mapping ) - Zahidah Ansari, Ansari (2013)
Wind turbine is a very good source of green energy. But building it needed a higher cost compare to other type of green energy. Therefore, choosing the right location to build the wind turbine is very important. Many cases have shown that if the location chosen is not appropriate, it will lead to pure lost since the turbine may not be able to function well. Besides that, choosing whether to build a low speed or high speed wind turbine is also important. This solely depends on the location chosen to build the turbine. Therefore the process of wind mapping is very important in the initial steps of building a wind turbine. During the wind mapping process, wind speed data of the chosen location is collected for a period of time. Usually from weeks up years. Then the sets of data are analyses, calculated and stimulated in graph. Later then when all the data have been analyses, calculated and stimulated we will know whether the location of studies is suitable or building wind turbine or not, and the type of wind turbine we should build. Later the data obtain is also used to study when is exactly the right time to use the wind turbine in its optimum condition as the wind speed varies throughout the whole year. From this we can alternate the usage of wind turbine energy and domestic electric supply. Although the effect may seem small, but we are actually minimizing energy waste due to excessive usage.